Import substitution processes in the material and technical support of vocational education programmes in the context of the movement towards technological sovereignty - V. I. Blinov; I. S. Sergeev; E. Yu. Esenina; A. I. Satdykov; S. A. Osadcheva (Russian State Vocational Pedagogical University, 2023)
Introduction. The vocational education system of any country is focused on training qualified personnel for the economy and is always closely connected with the socio-economic and foreign policy conditions for the development of the state. In the 2020s, the world community faced a number of challenges, including the Coronavirus pandemic, natural changes and cataclysms, and foreign policy conflicts. The problem of supporting the vocational education system in the conditions of instability is acquiring an international dimension.Aim. The current paper aims to present the results of the research on import substitution processes in the material and technical support of educational programmes of secondary vocational education and an assessment of the readiness of educational organisations for this activity in the context of the new economic conditions for the development of Russia, taking into account the foreign experience of friendly countries.Methodology and research methods. The present applied research uses the methodology of the general scientific level based on the analysis of documents and materials, which are publicly available on the nternet. The methods of comparative, criterion and cluster analysis, the method of analysis of necessity and sufficiency, methods of goal-setting and formalisation of expected results, the method of interpretation were employed.Results. The article presents the intermediate results of the study of the regional VET systems adaptation to new economic conditions. The proposed set of criteria and indicators can be useful to the executive authorities in the field of education, the administration of educational organisations to develop their strategy in the coming years. In the future, the authors plan to prepare appropriate methodological recommendations.Scientific novelty. Cluster approach was applied to analyse management strategies of colleges and technical schools for updating and import substitution of equipment.Practical significance. The authors propose the set of criteria and indicators for assessing the material and technical support of vocational education system in the context of import substitution and building technological sovereignty in the Russian Federation.